4CPS-017 Evaluation of pharmacists' input in anticoagulation clinic reviewing direct oral anticoagulants initiated in a secondary care hospital in london. (March 2019) - Grover, A; Wright, P; Antoniou, S; Jagjot, C
Abstract : Background: The National Institute for Health and Care Excellence (NICE) technology appraisals has made recommendations on four direct oral anticoagulants (DOACs). Local anticoagulation policy recommends all patients newly initiated on a DOAC should be followed-up in an anticoagulation clinic within 4 weeks. There is evidence suggesting that up to 30% of patients are dosed inappropriately according to their age, bodyweight and renal function. Purpose: To assess the dosing appropriateness of DOACs at initiation at the 1 month follow-up anticoagulation appointment in the clinic. Determine percentage of patients who are initiated on an appropriate dose. Determine percentage of patients that had an intervention made in their treatment plan at the clinic. Material and methods: Data was collected retrospectively over a period of 6 months from patient healthcare records from January 2018 to July 2018 for patients attending anticoagulant clinics. Results: Sixty–four per cent (n=118) of patients newly initiated on a DOAC were followed–up within 4 weeks. Ninety–two per cent (n=166) of patients were initiated on an appropriate dose of DOAC in accordance with product licence. Fifteen per cent (n=27) of patients had either a dose or DOAC changed, or DOAC stopped at the follow–up appointment by a pharmacist. The majority of alterations were due to incorrect documentation of weight, use of old blood test results and use of eGFR instead of calculated creatinine clearance (CrCl) using Cockroft and Gault. The majority of patients were followed up within a 4 week period. A significant proportion, 8% (n=17), required dose amendments, as initial dosing was incorrectly based on CrCL estimated by the hospital system which is based on e–GFR and not Cockroft and Gault in line with the product licences and clinical trials. Conclusion: Pharmacists have a clear role in ensuring appropriate dosing of DOACs and a reminder (and education) for non-specialist pharmacists on the importance of dosing based on CrCl with Cockroft and Gault, as opposed to the default on hospitals with is e-GFR. Reference and/or acknowledgements: Manzoor BS, Cheng WH, Lee JC, et al. Quality of pharmacist-managed anticoagulation therapy in long-term ambulatory settings: a systematic review. Ann Pharmacother 2017;51:1122–37. No conflict of interest.